Reconstitution of a nanomachine driving the assembly of proteins into bacterial outer membranes - Shen, Hsin-Hui (Nat Commun, 2014)
In biological membranes, various protein secretion devices function as nanomachines, and measuring the internal movements of their component parts is a major technological challenge. The translocation assembly module (the TAM) is a nanomachine required for virulence of bacterial pathogens. We have reconstituted a membrane containing the TAM onto a gold surface for characterization by Quartz Crystal Microbalance with Dissipation (QCM-D) and Magnetic Contrast Neutron Reflectrometry (MCNR). The MCNR studies provided structural resolution down to 1Å, enabling accurate measurement of protein domains projecting from the membrane layer. Here, we show that dynamic movements within the TamA component of the TAM are initiated in the presence of a substrate protein, Ag43, and that these movements recapitulate an initial stage in membrane protein assembly. The reconstituted system provides a powerful new means to study molecular movements in biological membranes, and the technology is widely applicable to studying the dynamics of diverse cellular nanomachines.